Islamofobia di Indonesia dan Tantangan Pewacanaannya: Islamophobia and the Challenges of its Discourse in Indonesia - Abdurrahman, Usamah; Al Hakim, Ahmad Hilmy Luqman (Journal of Islamic and Occidental Studies, 2025)
This paper aimed to situate the concept of islamophobia and portray its conditions in Indonesia. It first attempted to clarify the meaning of islamophobia by elaborating it as categorized by Ozcan Hidir into two categories: 1.0 and 2.0. From there, the author tried to point out a number of phenomena that illustrate the practice of islamophobia in Indonesia by classifying them based on three historical periods: before the Proclamation of Independence, from the Proclamation of Independence to the 9/11 and the Bali bombings, and from the 9/11 and the Bali bombings to the present.  With reference to these three periods, the author then analyzed that in the colonial era, islamophobia was generally practiced by the Dutch East Indies government to discipline the natives who positioned Islam as a symbol and spirit of collective resistance. In the second period, the disciplinary process was practiced by secular elites in the government circles in both the Soekarno and Soeharto periods. As for the third period, islamophobia applies in the form of eliminating certain groups of Muslims who are considered intolerant and labeled radicals, fundamentalists, and terrorists. From there, the author then clarified a number of arguments above that hinder the discourse of islamophobia in Indonesia. Based on Islamophobia 1.0 and 2.0, the author found that irrational hatred and fear of Islam or Muslims in Indonesia is real, as well as the branding or stereotyping of Islam and Muslims with certain negative terms to be generalized to all Muslims also occurs in this country.